Gender gaps in the downstream nodes of the rice value chain in Uganda: evidence and remedies - Kinkingninhoun Medagbe, Florent M.; Mujawamariya, Gaudiose; Twine, Edgar E.; Musana, Brian; Akongo, Thelma Flavia; Nabikyu, Jane (International Rice Research Institute, 2023)
Women are limitedly involved in post-production, downstream (DS) nodes of the rice value chain (RVC). In Uganda, only 8% of women own rice mills; women labourers to millers undertake marginal activities of cleaning, winnowing, etc. As rice marketing agents, women range between 5% and 30%, but their gains are not documented. The current study demonstrates gender differences in benefits derived from DSRVC nodes and factors that reduce gender gaps in remunerations. The study uses large-scale quantitative data from a survey conducted in 17 major rice growing and trading districts in Eastern Uganda covering 675 male and 187 female actors purposively selected at the key DSRVC nodes; the sample distribution represents gendered-engagement in DSRVC with absolute male dominance. The profitability analysis revealed, on average, an annual net income across the DSRVC of UGX 7,057,178 (1930 USD) in 2022, an increase, compared to UGX 5,821,751 (1590 USD) in 2021, male actors significantly gain twice or more the incomes gained by female actors; rice milling, and paddy collecting/marketing generate higher returns compared to other DSRVC business engagements. There were no gender differences in payments of labourers performing the same activity. An Oaxaca Blinder decomposition of income was done, revealing a disparity between men and women of 1.05. Among the predictors, experience in RVC with 39.04% contributed the most to the gap, then the number of years of schooling and being head of the household. For the DSRVC actors, the men's higher financial capacity, knowledge/skills/competencies, greater physical strength and the women's higher burden of reproductive activities and cultural norms explain the gender disparity in income. The remedial actions include facilitating women's access to suitable credit, sensitizing target communities on gender equality to access resources and markets, and training on businesses management for profitability. On-farm actions and facilitating access to extension service are also necessary.